DEKONSTRUKSI IDEOLOGI FEMINISME PADA KEHIDUPAN PEREMPUAN PESISIR PANTAI HYATT, SANUR-BALI - I Putu Wisnu Saputra; Awaluddin Hasrin (Labor Program Studi Pendidikan Sosiologi, 2022)
The purpose of this research is to provide an overview of the local problems of coastal life that tend to spread into global problems that are also faced by coastal women throughout Indonesia and even the world. The research approach used is qualitative research. Qualitative research is a type of research that is understood as research that utilizes descriptive data. data, namely in the form of data in the form of sentences both verbal and non-verbal. The subjects in this study were women from Hyatt beach, Sanur-Bali. The data collection techniques used are interviews, observation, documentation and literature study. The results of this study indicate that the economic life of Hyatt beach coastal women, Sanur-Bali is identical to the life of being a fisherman. Socio-cultural life of coastal women is seen in PKK activities, Mejejaitan together, and others. Domestic life of coastal women can be seen in cooking activities carried out when the husband has returned from fishing. Social problems experienced by coastal women of Hyatt beach, Sanu-Bali can be seen in various forms of discrimination that hit women.